Persepsi Warga Jakarta Terhadap Pelayanan Publik Dengan Metode IPA Dan CSI - Aloysius Rangga Aditya Nalendra*; Bryan Givan; Imelda Sari (Jurnal Ecodemica: Jurnal Ekonomi, Manajemen, dan Bisnis, 2020)
ABSTRACTThis study examines services performed at the first-level public service center, the kelurahan. This study aims to look at the perception of DKI Jakarta citizens towards public service in the Anis Baswedan era. This study used 1000 respondents with incidental techniques and sampling using the cluster sample method. This study examines service layouts in villages that are spread over 5 regions of DKI Jakarta, namely Central, East, North West and South Jakarta with measurement methods using the Natural Sciences and CSI methods. The results of this study are in general the citizens of DKI Jakarta are satisfied and the perception of public services received by citizens is positive with a CSI value of 66.35 and a Cartesian diagram in field B which means that the services provided are good and should be maintained. The perception of DKI Jakarta residents towards public services in urban villages during the era of Governor Anies Baswedan was positive. This is the global value of both CSI and IPA which has a positive impact which can be interpreted that the people of DKI Jakarta generally feel satisfied with the services provided to citizens through public services in the kelurahan. Only two areas of DKI Jakarta need to improve services so that the citizens of DKI Jakarta can be satisfied, namely the villages located in West Jakarta and East Jakarta.Keywords:  Importance-Performance Analysis, Customer Satisfaction Index